Efforts To Improve Ability To Memorize The Qur'an Hadiths Using The Murattal Al-Qur'an Disk On Students - Zaifatur Ridha; Hayatun Sabariah; Sonya Elsa Triyanda Pohan; Cici Rahmayani; Nurmaini Nurmaini (Indonesia, 2022)
Purpose the research is With the research title The Implementation of Disk Murattal Learning Media in Improving Learning Understanding of Al Quran Hadith in Class VII MTs Students. Private TarbiyahWaladiyahPulauBanyak. The problems found in the research location were: 1). The learning and teaching process in madrassas, teachers in the field of study of Al-qur'an hadith have not involved students directly with the digital Al-qur'an application from the subject matter of the Al-qur'an hadith study area taught so that students have not been trained in solving various field problems study of Al-qur'an hadith. 2). The unavailability of media that supports learning and teaching activities of Al-quran Hadith in madrasas. The focus of this research is that the researcher focuses on the application of Disk Murattal Media and the efforts made by the teacher in the Al-quran Hadith study field to improve students' reasoning abilities. 1). The influence of digital Al-quran-based Disk Murattal Media on students' reasoning abilities in the concept of understanding and memorizing Al-quran verses by students of the TarbiyahWaladiyah Island Many Private Tsanawiyah Madrasah is significant, namely the application of the model helps students to better understand the subject matter. 2). Improved reasoning skills of students on indicators of creative thinking, flexible thinking, original thinking, and detailed thinking after the application of Disk Murattal Media to students of TarbiyahWaladiyah Island Banyak Madrasah Tsanawiyah. 3). Student activities when applied to Disk Murattal Media in the Al-quran hadith study at Madrasah TsanawiyahTarbiyahWaladiyahPulauBanyak, students responded well